Approximately 1.78 Ga mafic dykes in the Lüliang Complex, North China Craton: Zircon ages and Lu‐Hf isotopes, geochemistry, and implications. (1st August 2014) - Wang, Xi; Zhu, Wenbin; Luo, Meng; Ren, Xingmin; Cui, Xiang
Abstract Mafic dyke swarms are excellent time markers and paleostress indicators. Numerous late Paleoproterozoic mafic dykes are exposed throughout the Trans‐North China Orogen (TNCO). Most of these dykes trend NW‐SE or NNW‐SSE, nearly parallel to the orogen, while a series of E‐W trending mafic dykes are restricted in the Lüliang and southern Taihang areas in the central segment of the TNCO. These dykes were mostly considered to be linked with breakup of the supercontinent Columbia previously. In this study, 16 mafic dykes were investigated in the Lüliang Complex. Zircon LA‐ICP‐MS dating of four samples yields magmatic crystallization ages of 1.78–1.79 Ga. These dykes belong to the tholeiite series and consist of basalt, basaltic andesite, and andesite. They are enriched in LREE and LILE and depleted in HFSE, and have negative zircon εHf(t) values of −1.7 to −12.2. The E‐W trending mafic dykes show similar geochemical and isotopic features compared to the NW‐SE trending dykes in other complexes. They were most likely originated from a lithospheric mantle metasomatized by subduction‐related fluids and later emplaced along extensional fractures in a postcollisional setting. NW‐SE trending fractures were formed due to gravitational collapse and thinning of the lithosphere. E‐W trending fractures in the central segment of the orogen constitute a transverse accommodation belt to equilibrate the different amounts of extension between the northern and southern TNCO. The impact of the postorogenic extension might have continued to approximately 1680 Ma as evidenced by the presence of abundant approximately 1750–1680 Ma anorthosite‐gabbro‐mangerite‐rapakivi granite suites (AMCG‐like) occurring in the northern NCC.